The Methodology of Realizing Mystical Facts according to Ibn Arabi and Sadrolmote'allehin - Alireza Jalali (حکمت صدرایی, 2017)
In the present article, first, we highlight Ibn Arabi's surprising influence on Sadrolmote'allehin. This is such that the latter has referred to the former in his most innovative aspects of his wisdom and mysticism. The study of the major works of Sadrolmote'allehin, such as Asfar, Mafatih Alghyb, Shawahid AL-Rububiyah...., as well as a look at Futuhat al-Makkiyya and Ibn al-Arabi’s Fusus al-Hikam suggests that both of them, in solving complex problems, have spoken of discovery and intuition; they have described their works as inspirational and regard themselves as inspirational agents of their statements.Ibn Arabi, in his works, on the one hand, contemplates in accordaance with the commonly used logical criteria and criteria, but, on the other hand, sees the discovery and intuition as the most genuine criterion of awareness and understanding. Sadrolmote'allehin also believes that in order to receive occult inspirations, one must, in addition to having the health in his nature, have broadmindedness, acumen, and the speed of understanding along with discovery, and be subject to Divine providence, so that a light would be sent from God to make him shine like a lamp.